2015
DOI: 10.18632/oncotarget.4210
|View full text |Cite
|
Sign up to set email alerts
|

miR-620 promotes tumor radioresistance by targeting 15-hydroxyprostaglandin dehydrogenase (HPGD)

Abstract: MicroRNA contribute to tumor radiation resistance, which is an important clinical problem, and thus we are interested in identifying and characterizing their function. We demonstrate that miR-620 contributes to radiation resistance in cancer cells by increasing proliferation, and decreasing the G2/M block. We identify the hydroxyprostaglandin dehydrogenase 15-(nicotinamide adenine dinucleotide) (HPGD/15-PGDH) tumor suppressor gene as a direct miR-620 target, which results in increased prostaglandin E2 (PGE2) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 59 publications
0
19
0
1
Order By: Relevance
“…HPGD was initially characterized as a key enzyme responsible for biological inactivation of prostaglandins 25 and subsequently shown to be involved in a number of human malignancies 22 , 40 – 42 . miR-620 is reported to up-regulate PGE2 expression by directly targeting HPGD, contributing to tumor radiation resistance 43 . An earlier study by He et al demonstrated that miR-21 participates in tumorigenesis via targeting the HPGD/PGE2 signaling pathway 44 .…”
Section: Discussionmentioning
confidence: 99%
“…HPGD was initially characterized as a key enzyme responsible for biological inactivation of prostaglandins 25 and subsequently shown to be involved in a number of human malignancies 22 , 40 – 42 . miR-620 is reported to up-regulate PGE2 expression by directly targeting HPGD, contributing to tumor radiation resistance 43 . An earlier study by He et al demonstrated that miR-21 participates in tumorigenesis via targeting the HPGD/PGE2 signaling pathway 44 .…”
Section: Discussionmentioning
confidence: 99%
“…miRNA are involved in all cell processes and have been of particular interest due to their role in cancer. They have been implicated in cell cycle progression, metastatic progression, and treatment response (Huang et al ., , ; Mesci et al ., ). Individual miRNA can regulate thousands of cellular pathways simultaneously (Huntzinger and Izaurralde, ).…”
Section: Introductionmentioning
confidence: 99%
“…Transcript degradation is the major outcome of miRNA-mRNA binding, occurring through the 5 0 -to-3 0 mRNA decay pathway (Huntzinger and Izaurralde, 2011). miRNA are involved in all cell processes and have been of particular interest due to their role in cancer. They have been implicated in cell cycle progression, metastatic progression, and treatment response (Huang et al, 2013(Huang et al, , 2015Mesci et al, 2017). Individual miRNA can regulate thousands of cellular pathways simultaneously (Huntzinger and Izaurralde, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that miR‐620 was overexpressed in human lung adenocarcinoma and regulated proliferation, invasion and migration of adenocarcinoma cells via targeting the tumor suppressor gene Glypican 5 24 . Another study in different types of cancer cells showed that the excessive expression of miR‐620 induced cell proliferation, deregulated G2/M checkpoint in vitro, and enhanced radiation resistance in vivo 25 . Here, we reported for the first time that miR‐620 knockdown suppressed TGF‐β1‐induced proliferation and increased apoptosis in ASMCs.…”
Section: Discussionmentioning
confidence: 99%